Interlocking Train Control Integrated System Modeling Design Based on AADL. (January 2020) - Song, Zeyu; Li, Guoning
Abstract: In view of the characteristics of high-speed railway signal system due to its huge structure and complex fault phenomenon, the structure and function of the interlocking train control integrated system was designed by analyzing the important components of the computer interlocking and train control center. The computer interlocking, train control center and interlocking train control integrated system are designed and modeled by architecture analysis and design language (AADL). According to the specific requirements of high-speed railway signal system, reasonable AADL components are adopted in the modeling.